Effects of 5-week brain endurance training on fatigue and performance in elite youth epée fencers - Varesco, G.; Staiano, W.; Bracco, M.; Pageaux, B.; Soulas, L.; Goisbault, M.; Doron, J.; Jubeau, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To examine the effectiveness of 5 weeks of brain endurance training (BET) in reducing impairments in sustained attention, performance at a specific fencing test, and perceived fatigue after a cognitive fatiguing task in youth épée elite fencers during the preseason. Methods: Using a quasi-randomized controlled trial, 19 elite youth fencers (8 women, 18 [1] y) were divided into a BET (n = 11) or control (n = 8) group. Both groups trained for 5 sessions/wk during 5 weeks. The BET group completed the BET sessions before, during, or after fencing training, 3 or 4 times a week. The control group performed only fencing training. Before and after the 5 weeks, fencers performed a psychomotor vigilance test and fencing test before and after 40 minutes of a reverse Stroop task. Perceived fatigue was scored on a 10-cm visual analog scale. Results: After 5 weeks, perceived fatigue, reaction time, and number of lapses in the psychomotor vigilance test increased from before to after the reverse Stroop task only in the control group (P = .011), with no pre-to-post difference for the BET group (P > .059). No differences were found in fencing-test performance (P > .07). Effort for the reverse Stroop task increased for both groups after the 5 weeks (P = .043). We observed an increase in perceived fatigue, reaction time, and number of lapses in the BET group before the fatiguing task (P = .028). Conclusion: BET reduced the negative effects of a cognitive fatiguing task on sustained attention, without a clear improvement in performance on the fencing test, and represents a possible tool to mitigate fatigue in fencing.